Recurrent Arterial and Venous Thrombotic Events in a Patient with Psoriasis. Impact of PAI-1 Polymorphism: A Case Report - Borislav Dimitrov; Veronika Gincheva; Iva Simeonova; Anika Ivanova; Maria Petkova; Dimitar Gospodinov (Journal of Biomedical & Clinical Research)
Psoriasis isachronic autoimmune multisystem disease, mainly affecting the skin and joints. Its origin is related to both environmental and genetic factors. The condition affects 1-3%of the population worldwide. Psoriasis is also associated with cardiovascular risk factors, atherothrombotic events, and markers of hypercoagulation (platelet activation and hyperhomocysteinemia). Venous thromboembolism (VTE) isawidespread severe disease. Both VTEand psoriasis are connected with risk factors for cardiovascular disorders (obesity and hypertension). The incidence of VTEevents in patients with psoriasis is higher. Patients with psoriasis should be checked for risk factors (metabolic disorders and cardiovascular diseases).We reportacase of a 53-year old man, diagnosed with plaque psoriasis 20 years ago, andafive year history of hypertension. In 2006, he hadastroke, and in 2011 ‒aheart attack. In 2013 he was diagnosed with thrombophlebitis. The patient was recently diagnosed with Type IIdiabetes, dyslipidemia and metabolic syndrome. The DNAanalysis revealed that the patient wasahomozygous carrier of 4G/4G (rs1799889) polymorphism in plasminogen activator inhibitor 1 (PAI-1) -a risk factor for thrombophilia. This case is important because of the major comorbidities, more particularly thrombotic events in combination withaprothrombotic mutation.